The Meaning of Hijrah among Niqobers in Social Media - Penny Respati Yurisa; Muassomah Muassomah; Irwan Abdullah (Analisa: Journal of Social Science and Religion, 2020)
Hijrah conception has experienced a shift of meaning between its concept in the Prophet's era and today. Hijrah is often associated with the use of niqob and radicalism. By wearing niqob as a means of hijrah, someone does not merely modify her fashion, but also her behavior. There is also an assumption that those who are not wearing niqob have yet to hijrah. This research aims to ﬁnd out the concept of hijrah for women with niqob, including the background and the inﬂuence of the concept of hijrah on their religiosity. This study employs a descriptive qualitative research method. The data were collected from chats in a Niqober group, in which a discussion on hijrah was conducted. The conversations were captured, selected, sorted, classiﬁed, and displayed in tables. Then, the data were analyzed descriptively and iteratively. The results of this study indicate that today, hijrah has three concepts: a change in circumstance, a change in behavior, and a change in fashion. Wearing a niqob, as a form of hijrah, is inﬂuenced by some factors, such as the factors of partner, family, and environment. The concept of hijrah for Niqobers inﬂuences the meaning in religion. First, hijrah is symbolized with the use of niqob. Second, a woman who does hijrah by wearing niqob is considered to be radical. Third, hijrah using niqob means following the Arabic culture. This study suggests conducting an education related to the concept of hijrah that are believed by the Niqobers. To use niqob does not only mean hijrah, but also it is the Prophet's sunnah, and it is not obligated. Therefore, it cannot be assumed that women who do not wear niqob have yet to commit hijrah.